'The sad aperture of the dead': Colson Whitehead's Zone One and the anti-blackness of the book as an object. Issue 12 (2nd December 2021) - McCoy, Beth A.; Montgomery, Jasmine Y.
ABSTRACT: Colson Whitehead's Zone One (2011) appropriates as its structuring metaphor the architecture of New York City's African Burial Ground National Monument. More specifically, the novel likens its book form to the Burial Ground memorial's Ancestral Chamber, a granite portal–an aperture–that offers memorial visitors a glimpse of slavery's world swirling on the other side. In doing so, Zone One suggests that the book as an object is anti-black, its letters, words, lines, paragraphs, and pages composed of nothing more than the accumulation of slavery's dead. Through Atlantic imagery, print jokes, and protagonist Mark Spitz's discovery of himself dead in a dictionary, Zone One implicates all modern books as manifestations of what the narrator terms the 'sad aperture of the dead': a site where Atlantic and textual accumulation meet, the former expressed as water and liquidity, the latter as typographical 'density'. In recapitulating the African Burial Ground's mapping, Zone One echoes Dionne Brand's theory of the 'Door of No Return' that identifies the diaspora's 'cognitive schema' as captivity.